2021
DOI: 10.1088/2053-1583/ac2a73
|View full text |Cite
|
Sign up to set email alerts
|

Graphdiyne/CdSe quantum dot heterostructure for efficient photoelectrochemical water oxidation

Abstract: The design and synthesis of efficient catalysts for water oxidation is of significant importance. Here a type of graphdiyne (GDY) based heterostructure of CdSe/GDY was synthesized through a facile in-situ growth strategy including the first growth of GDY nanosheet arrays followed by the nucleation and growth of CdSe quantum dots (QDs) featuring well-dispersed CdSe QDs with uniform size around 3 nm. Experimental results revealed that GDY could effectively induce the growth and well-dispersion of CdSe QDs on GDY… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…The results showed that the CdSe/GDY as grown on GDY can achieve greatly enhanced photoactivity and oxygen production under light illumination. 131 Inspired by the controllable synthesis of GDY-based quantum dot catalysts, metal clusters have also been successfully loaded on GDY for efficient catalysis. Gao et al 132 grew VRu 0.027 O x clusters (2.75 AE 0.04 nm) that were uniformly dispersed on the surface of GDY without agglomeration.…”
Section: Graphdiyne-based Quantum Dot Catalystsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that the CdSe/GDY as grown on GDY can achieve greatly enhanced photoactivity and oxygen production under light illumination. 131 Inspired by the controllable synthesis of GDY-based quantum dot catalysts, metal clusters have also been successfully loaded on GDY for efficient catalysis. Gao et al 132 grew VRu 0.027 O x clusters (2.75 AE 0.04 nm) that were uniformly dispersed on the surface of GDY without agglomeration.…”
Section: Graphdiyne-based Quantum Dot Catalystsmentioning
confidence: 99%
“…The results showed that the CdSe/GDY as grown on GDY can achieve greatly enhanced photoactivity and oxygen production under light illumination. 131…”
Section: Graphdiyne-based Catalytic Materialsmentioning
confidence: 99%
“…Hybrid organic–inorganic perovskites are a class of materials whose power conversion efficiency (PCE) in solar cell applications has dramatically increased from 3.8% in 2009 to 25.7% in 2020. These improvements have spurred intensive research to break the 30% PCE barrier, approach the Shockley–Queisser limit, increase the stability and longevity of the perovskites, reduce usage of environmentally problematic compounds, and relevant to this study, expand control over the materials at the level of electronic structure. Two-dimensional (2D) materials are unmatched in their ability to realize finely tunable optoelectronic properties through simple changes such as pressure modification, modulation in the number of layers, and exchange of interfacing materials. This flexibility has led to successful application of 2D perovskites (2DPKs) as efficient light emitters, photodetectors, and hybrid photovoltaic (PV) and thermoelectric (TE) materials. The 2D analogues of standard AB X 3 bulk hybrid perovskites (where A is an organic cation, B is Pb, Sn, or Ge, and X is a halogen anion) take the form of A′ 2 A n –1 B n X 3 n +1 . In hybrid 2DPKs, A′ is an organic cation generally of longer length than A, which acts as a spacer between the 2D or quasi-2D perovskite layers, n is the number of layers, and the identity of A, B, and X remains the same.…”
Section: Introductionmentioning
confidence: 99%
“…84,85 Lastly, the ultrathin thickness of the GDY layers greatly shortens the transfer distance of the charge carriers to their surface, efficiently improving the separation efficiency of photo generated charge carriers. 86,87 Heterojunction architectures based on GDY materials is Up to now, numerous experimental efforts have been devoted into the development of GDY-based heterojunction with other semiconductors, such as MoS 2 , 88,89 TiO 2 , 90,91 g-C 3 N 4 , 92 NiFe layered double hydroxide (LDH), 93,94 CdS, 95,96 CuS, 97 CdSe, 98 CoS, 99,100 graphene 101,102 and so on. Li 0 s group realized in-situ growth of ultrathin molybdenum disulfide (MoS 2 ) on the surface of electron-rich GDY using a facile solvothermal strategy.…”
Section: Heterojunction Of Gdymentioning
confidence: 99%
“…Up to now, numerous experimental efforts have been devoted into the development of GDY‐based heterojunction with other semiconductors, such as MoS 2 , 88,89 TiO 2 , 90,91 g‐C 3 N 4 , 92 NiFe layered double hydroxide (LDH), 93,94 CdS, 95,96 CuS, 97 CdSe, 98 CoS, 99,100 graphene 101,102 and so on. Li′s group realized in‐situ growth of ultrathin molybdenum disulfide (MoS 2 ) on the surface of electron‐rich GDY using a facile solvothermal strategy 103 .…”
Section: Design and Synthesis Of Gdymentioning
confidence: 99%